Perbandingan Penerapan Corporate Social Responsibility (CSR) pada PT Bukaka Teknik Utama Tbk dengan PT Adhi Karya Tbk - Sri Suryaningsum; Muhammad Irhas Effendi; R. Hendri Gusaptono; Sri Wahyuni (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
This study aims to determine and obtain empirical evidence about the comparative implementation of Corporate Social Responsibility (CSR) in PT Bukaka Teknik Utama Tbk and PT AdhiKaryaTbk. Corporate Social Responsibility (CSR) is carried out policies of a company as a concern and their responsibilities towards the environment and surrounding communities. In this study, using literature review to compare Corporate Social Responsibility (CSR) between PT Bukaka Teknik Utama Tbk and PT Adhi Engineering Tbk in 2013-2015.The results showed that CSR conducted by PT Bukaka Teknik Utama Tbk meet the health, social and community development. While CSR PT AdhiKaryaTbkmeets all aspects that support CSR, and they are always thinking of innovative CSR program was excellent in every year.